PENGARUH PERKEMBANGAN BANDARA INTERNASIONAL ADI SOEMARMO TERHADAP PERUBAHAN PENGGUNAAN LAHAN DI SEKITARNYA - Salindri Kusumawati; Kuswanto Nurhadi; Erma Fitria Rini (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2016)
The need for air transportation always increases every year in Indonesia. It can be seen from the increasing number of aircraft passenger. Airport as an air transport infrastructure which serves flights is considered necessary to develop. Adi Soemarmo International Airport is the one that do some development in order to solve those needs. Developing the airport may influence the surrounding area with improving the infrastructures of the region. Thus, the area around the airport has a relative growth expanded faster than other regions. Issue that appointed in this paper was how to influence the development of Adi Soemarmo International Airport changes the land use on this area? The purpose of this study is to determine the effect of the development of Adi Soemarmo International Airport changes the land use on this area. This study uses a deductive approach and is classified as descriptive research. The analysis technique used not only scoring analysis to assess the development of the international airport Adi Soemarmo but also an explanatory descriptive analysis using qualitative matrix to assess the influence of the influence of the Adi Soemarmo International Airport to each of the sub-variables on aspects of land use changes. This study concluded that the development of Adi Soemarmo International Airport have a strong influence on changes in the types of land use in the area and have a fair influence on changes in land use in the surrounding area.